Gotong Royong in Political Unrest: Reclaiming Solidarity Through the Warga Jaga Warga Movement - Illahiati, Nisa Kurnia (Jurnal Media dan Komunikasi, 2025)
This article examines the emergence of the Warga Jaga Warga movement during Indonesia’s 2025 wave of student-led demonstrations and political unrest. Originating as a digital slogan circulated on social media platforms, Warga Jaga Warga rapidly expanded into offline practices such as neighborhood patrols, vigilance posts, and community deliberations. Using a qualitative case study approach, the research draws on policy documents, media reports, and secondary literature to analyze how the movement mobilized civic participation through digital and cultural repertoires. The study situates Warga Jaga Warga within social movement theory and media activism frameworks, emphasizing the role of framing processes in linking online slogans with offline practices. The findings reveal that the cultural philosophy of gotong royong, which highlights Indonesia’s ethic of mutual cooperation, served as the reflective framework that legitimized and sustained the movement. By invoking gotong royong, participants understood their actions not as exceptional but as continuations of deeply rooted traditions of solidarity. This cultural grounding enabled the digital slogan to resonate widely, translating connective action into enduring collective practices. At the same time, the movement demonstrated ambivalence; while reinforcing stability and relieving state burdens, it risked co-optation by local authorities and raised questions about balancing civic order with democratic protest rights. The paper concludes that Warga Jaga Warga illustrates how cultural philosophies can anchor digital activism, offering a distinctive contribution to the study of grassroots solidarity in Indonesia’s democratic landscape.